Brazilian recommendations on the safety and effectiveness of the yellow fever vaccination in patients with chronic immune-mediated inflammatory diseases - Pileggi, Gecilmara Salviato (2019)
Background: In Brazil, we are facing an alarming epidemic scenario of Yellow fever (YF), which is reaching the most populous areas of the country in unvaccinated people. Vaccination is the only effective tool to prevent YF. In special situations, such as patients with chronic immune-mediated inflammatory diseases (CIMID), undergoing immunosuppressive therapy, as a higher risk of severe adverse events may occur, assessment of the risk-benefit ratio of the yellow fever vaccine (YFV) should be performed on an individual level. Main body of the abstract: Faced with the scarcity of specific orientation on YFV for this special group of patients, the Brazilian Rheumatology Society (BRS) endorsed a project aiming the development of individualized YFV recommendations for patients with CIMID, guided by questions addressed by both medical professionals and patients, followed an internationally validated methodology (GIN-McMaster Guideline Development). Firstly, a systematic review was carried out and an expert panel formed to take part of the decision process, comprising BRS clinical practitioners, as well as individuals from the Brazilian Dermatology Society (BDS), Brazilian Inflammatory Bowel Diseases Study Group (GEDIIB), and specialists on infectious diseases and vaccination (from Tropical Medicine, Infectious Diseases and Immunizations National Societies); in addition, two representatives of patient groups were included as members of the panel. When the quality of the evidence was low or there was a lack of evidence to determine the recommendations, the decisions were based on the expert opinion panel and a Delphi approach was performed. A recommendation was accepted upon achieving ≥80% agreement among the panel, including the patient representatives. As a result, eight recommendations were developed regarding the safety of YFV in patients with CIMID, considering the immunosuppression degree conferred by the treatment used. It was not possible to establish recommendations on the effectiveness of YFV in these patients as there is no consistent evidence to support these recommendations. Conclusion: This paper approaches a real need, assessed by clinicians and patient care groups, to address specific questions on the management of YFV in patients with CIMID living or traveling to YF endemic areas, involving specialists from many areas together with patients, and might have global applicability, contributing to and supporting vaccination practices. We recommended a shared decision-making approach on taking or not the YFV.